Econometric and Computational Issues in Estimating Demand for Energy by Time-of-Day - Ramanathan, Ramu; Mitchem, Allen (The Review of Economics and Statistics, 1982)
A two-step time-series and cross-section model is used to estimate time-of-day (TOD) demand for electricity or natural gas and to demonstrate an efficient computational method. Post-sample validation of the model results in several regions found average forecast errors in the aceptable range of 4.5% to 15%. Future hourly electricity-demand forecasts made for 32 regions using an historical trend scenario and a Data Resources Inc. macro model scenario indicate a good potential for the model. 12 references. (DCK)